Malaria is the leading cause of acute kidney injury among a Zambian paediatric renal service cohort retrospectively evaluated for aetiologies, predictors of the need for dialysis, and outcomes. - Chisambo Mwaba; Sody Munsaka; Bruce Bvulani; David Mwakazanga; Brian Chanda Chiluba; Kaiser Fitzwanga; Evans Mpabalwani (PLoS ONE, 2023)
Background Whilst malaria is a prominent aetiology associated with acute kidney injury (AKI) in many parts of Africa, a shift in the traditional AKI aetiologies has been witnessed in sections of the continent. Additionally, limited access to dialysis worsens patient outcomes in these low-resource settings. This retrospective cross-sectional study aimed to determine the associated aetiologies, predictors of need for dialysis and malaria-associated AKI (MAKI), and outcomes of AKI and dialysis among children evaluated by the renal service in Lusaka, Zambia. Methods The study sampled all children aged 16 years or below, diagnosed with AKI between 2017 and 2021, by the renal unit at the University Teaching Hospitals- Children's Hospital (UTH-CH), and retrospectively abstracted their records for exposures and outcomes. AKI was defined using the Kidney Disease Improving Global Outcomes (KDIGO) 2012 criteria. Frequency and percentage distributions were used to describe the occurrence of AKI aetiologies and treatment outcomes. Predictors of the need for dialysis, MAKI, and poor treatment outcome were identified by using multivariable logistic regression models. Results A total of 126 children diagnosed with AKI were included in this study. Malaria was the most frequent aetiology of AKI(61.1% (77/126, 95% Confidence Interval (CI): 52.0%-69.7%)). Of the 126 children with AKI, 74.6% (94) underwent dialysis. Predictors of the need for dialysis were oliguria (p = 0.0024; Odds ratio (OR) = 7.5, 95% CI: 2.1-27.7) and anuria (p = 0.0211; OR = 6.4, 95% CI = 1.3, 30.7). A fifth (18.3%, 23/126) of the children developed chronic kidney disease (CKD), 5.6% (7/126) died and, a year later, 77% (97/126) were lost to follow-up. Conclusion At UTH-CH, malaria is the most frequent aetiology among children with AKI undergoing dialysis and children from low-medium malaria incidence areas are at risk; a considerable proportion of children with AKI need dialysis and Tenchoff catheter use in AKI is advocated.